PROLACTIN SERUM LEVELS IN PEMPHIGUS PATIENTS - Thai Van, Thong; Doan Van Loi, Em; Le Ngoc, Diep; Nguyen Trong, Hao (Tạp chí Da liễu học Việt Nam, 2025)
Objective: Pemphigus is an autoimmune blistering disease. Prolactin is a hormone that affects the immune system; elevated serum prolactin levels may reduce the destruction of autoimmune B-cell lines, lower the activation threshold of B-cells, and promote autoimmune responses. This study aims to investigate the difference in serum prolactin levels between pemphigus patients and a control group. Subjects and Methods: A case-control study was conducted on 30 pemphigus patients and 20 controls who visited Ho Chi Minh City Dermatology Hospital between January 20, 2022, and September 30, 2022, for serum prolactin level testing. Results: Serum prolactin levels were significantly higher in the pemphigus group compared to the control group [12.9 (9.2 – 20.1) ng/ml vs. 6.7 (4.3 - 9.5) ng/ml; p = 0.0001]. The study also found a moderate positive correlation between serum prolactin levels and the extent of skin lesions in the patient group (r = 0.39, p = 0.03). Conclusion: Serum prolactin levels were significantly higher in pemphigus patients compared to the control group. Received 20 November 2023 Revised 27 December 2023 Accepted 28 February 2024